Central banks - independent or almighty? - Otmar Issing (Leibniz Institute for Financial Research SAFE, 2021)
Historically Central Bank Independence (CBI) was anything but the norm. CBI seems to contradict core principles of democracy. Most economists were also against CBI. After the Great Inflation of the 1970ies many empirical studies demonstrated that there is a strong negative correlation between the degree of CBI and the rate of inflation. In 1990 most major countries had endowed their central bank with the status of independence. Overburdening with elevated expectations and additional competences are threatening the reputation of central banks and undermining the case for CBI.
urn:nbn:de:hebis:30:3-552344
Keywords: 330; Central banks